2018
DOI: 10.1128/jvi.02011-17
|View full text |Cite
|
Sign up to set email alerts
|

eCD4-Ig Variants That More Potently Neutralize HIV-1

Abstract: The human immunodeficiency virus type 1 (HIV-1) entry inhibitor eCD4-Ig is a fusion of CD4-Ig and a coreceptor-mimetic peptide. eCD4-Ig is markedly more potent than CD4-Ig, with neutralization efficiencies approaching those of HIV-1 broadly neutralizing antibodies (bNAbs). However, unlike bNAbs, eCD4-Ig neutralized all HIV-1, HIV-2, and simian immunodeficiency virus (SIV) isolates that it has been tested against, suggesting that it may be useful in clinical settings, where antibody escape is a concern. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 53 publications
(80 reference statements)
0
23
0
Order By: Relevance
“…Previous studies have shown that incubation of cell-expressed Env trimers with soluble CD4 (sCD4) or CD4-Ig promoted dissociation of gp120 from gp41, a phenomenon described as "shedding" (48). We have previously shown that eCD4-Ig promotes more efficient shedding than CD4-Ig (45). We therefore investigated whether e10-1074 promoted greater shedding than 10-1074.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have shown that incubation of cell-expressed Env trimers with soluble CD4 (sCD4) or CD4-Ig promoted dissociation of gp120 from gp41, a phenomenon described as "shedding" (48). We have previously shown that eCD4-Ig promotes more efficient shedding than CD4-Ig (45). We therefore investigated whether e10-1074 promoted greater shedding than 10-1074.…”
Section: Resultsmentioning
confidence: 95%
“…Here we investigated whether the coreceptor-mimetic peptide mim6 (45) fused to the C termini of bNAbs of various classes could improve their neutralization as it does for CD4-Ig. We observed that mim6 consistently improved the potency of all V3-glycan antibodies tested, whereas it improved the potency of all other bNAb classes only for Envs that could be neutralized by the peptide alone.…”
mentioning
confidence: 99%
“…For instance, Xu et al reported that a trispecific bnAb conferred complete immunity against a mixture of SHIVs in macaques that otherwise show resistance to single monospecific bnAbs (28). Recent studies also demonstrated the robust and sustained antiviral effects of engineered bnAbs with eCD4 as a component, given the fact that all HIV-1 isolates, including those few which can enter cells using only a coreceptor, bind to the primary HIV-1 receptor CD4 (41). In this study, we observed that a single-dose infusion of the bispecific multivalent eCD4-based bnAb LSEVh-LS-F resulted in rapid virological control in chronically SHIV-infected macaques without the development of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the coreceptor-mimetic peptide also limits CD4enhancement on CD4-negative/CCR5-positive cells. Recently we have shown that three mutations in CD4 domain 1 increase its potency by an average of 9-fold (Fetzer et al, 2018). Furthermore, in vitro studies showed that continuous passaging of virus in the presence of eCD4-Ig only yielded partial resistance to the inhibitor (Fellinger et al, 2019).…”
Section: Engineered Hiv-1 Inhibitorsmentioning
confidence: 99%